Innovations Healthy Drinks in Source of Soybean in Community Empowerment through Entrepreneurship in Sukoharjo District - Sholichah Rohmani; Adi Yugatama; Fea Prihapsara (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Community service activities with IbM scheme have been done in home industry of soybean milk processing in Sraten and Kartasura Village, Sukoharjo District. The aim of activities are all partners able process soybean juice into health drink product in ready to drink packaging, adn next can be as new economic commodity to the community. In addition, partners are expected to have a clear administrative and governance system in finance, production and, marketing as an effort to empower communities in Sukoharjo District. Considering the benefits of this soy essence is so great then product diversification is needed so that the product is more acceptable to the market. This program is done through several stages namely 1) Making soybeans into ready-to-drink; 2) Transfer of packing technology; 3) Product marketing and management aspects of soybean processing into beverages in ready-to-drink packaging as well as; and 4) Feasibility analysis of beverage production business made from soybean. Through IbM, training and development of soya bean processing technology is made into an economic commodity product in the form of beverages in ready-to-drink packaging, which can provide new economic alternatives in the community. After this program, the community service activity was conducted with the training and mentoring approach to the two partners, it was able to increase the quantity and quality of soybean beverage production where the yield of production increased almost twice from the original.